Effect of Dietary Supplementation of Spirulina platensis on the Growth and Haematology of the Stressed Catfish Clarias gariepinus - Sayed, Alaa Hamid; fawzay, Mostafa A. (JOURNAL OF ADVANCES IN BIOLOGY, 2014)
The effect of feeding Spirulina platensis on the growth and haematological parameters of the Nile catfish; Clarias gariepinus exposed to food shortage stress were investigated. S. platensis was added to the basal diet at 0.0, 1.25, 2.5 and 5.0 g Spirulina /kg diet and fed for two months to the Nile catfish. Our results showed that the ï¬nal fish weight, weight gain and specific growth rate of C. gariepinus fed on the experimental diets were not significantly different (p > 0.05). The fish fed on Spirulina diets exhibited higher RBCs counts, WBCs counts, haemoglobin and haematocrit levels as compared with stressed fish and control. The feeding dietary Spirulina resulted in significant decreases in mean cell volume, mean cell haemoglobin and neutrophils, while, the mean cell haemoglobin concentration was not affected. The platelets and monocytes were increased with Spirulina levels increase. A significant decrease in eosinophils and small lymphocytes were observed in the fish treated with Spirulina, however, the large lymphocytes were increased. The percentage of altered erythrocytes of fish treated with Spirulina was significantly decreased in comparison to stressed fish and control. We can conclude that Spirulina supplementation is promising for improving the hametological parameters in Clarias gariepinus, as immun-inducer and growth factor in food ingredients for fish feeding.